Dietary Approaches to Stop Hypertension via Indo-Mediterranean Foods, May Be Superior to DASH Diet Intervention - Singh, Ram B; Nabavizadeh, Fatemeh; Fedacko, Jan; Pella, Dominik; Vanova, Natalia; Jakabcin, Patrik; Fatima, Ghizal; Horuichi, Rie; Takahashi, Toru; Mojto, Viliam; Juneja, Lekh; Watanabe, Shaw; et al. (Nutrients, 2022)
Western-type diet with high salt and sugar, sedentary behavior, obesity, tobacco and alcoholism are important risk factors for hypertension. This review aims to highlight the role of western diet-induced oxidative stress and inflammation in the pathogenesis of hypertension and the role of various types of diets in its prevention with reference to dietary approaches to stop hypertension (DASH) diet. It seems that it is crucial to alter the western type of diet because such diets can also predispose all CVDs. Western diet-induced oxidative stress is characterized by excessive production of reactive oxygen species (ROS) with an altered oxidation-reduction (redox) state, leading to a marked increase in inflammation and vascular dysfunction. Apart from genetic and environmental factors, one important cause for differences in the prevalence of hypertension in various countries may be diet quality, deficiency in functional foods, and salt consumption. The role of the DASH diet has been established. However, there are gaps in knowledge about the role of some Indo-Mediterranean foods and Japanese foods, which have been found to decrease blood pressure (BP) by improving vascular function. The notable Indo-Mediterranean foods are pulses, porridge, spices, and millets; fruits such as guava and blackberry and vegetables, which may also decrease BPs. The Japanese diet consists of soya tofu, whole rice, in particular medical rice, vegetables and plenty of fish rich in fish oil, fish peptides and taurine that are known to decrease BPs. Epidemiological studies and randomized, controlled trials have demonstrated the role of these diets in the prevention of hypertension and metabolic diseases. Such evidence is still meager from Japan, although the prevalence of hypertension is lower (15-21%) compared to other developed countries, which may be due to the high quality of the Japanese diet. Interestingly, some foods, such as berries, guava, pumpkin seeds, carrots, soya beans, and spices, have been found to cause a decrease in BPs. Omega-3 fatty acids, fish peptide, taurine, dietary vitamin D, vitamin C, potassium, magnesium, flavonoids, nitrate and l-arginine are potential nutrients that can also decrease BPs. Larger cohort studies and controlled trials are necessary to confirm our views.
Keywords: western diet; anti-inflammatory foods; Vitamins; Diet; vitaminy; Hypertension; Vegetables; randomizované kontrolované studie jako téma; zelenina; krevní tlak; Randomized Controlled Trials as Topic; hypertenze; dieta; Dietary Approaches To Stop Hypertension; ovoce; Fruit; high blood pressure; DASH dieta; Blood Pressure; Mediterranean diet